2017
DOI: 10.2967/jnumed.116.186460
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation Between Brown Adipose Tissue 18F-FDG Uptake and Thermogenesis in Uncoupling Protein 1–Deficient Mice

Abstract: 18 F-FDG PET imaging is routinely used to investigate brown adipose tissue (BAT) thermogenesis, which requires mitochondrial uncoupling protein 1 (UCP1). It remains uncertain, however, whether BAT 18 F-FDG uptake is a reliable surrogate measure of UCP1-mediated heat production. Methods: UCP1 knockout (KO) and wild-type (WT) mice housed at thermoneutrality were treated with the selective b3 adrenergic receptor agonist CL 316, 243 and underwent metabolic cage, infrared thermal imaging and 18 F-FDG PET/MRI experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
64
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 17 publications
10
64
2
Order By: Relevance
“…In this respect, the present studies are also an in vivo extension of earlier studies showing that UCP1 is not a prerequisite for adrenergically induced glucose uptake in cultured brown adipocytes [46] or in intact mice [47]. In contrast, Inokuma et al.…”
Section: Discussionsupporting
confidence: 76%
“…In this respect, the present studies are also an in vivo extension of earlier studies showing that UCP1 is not a prerequisite for adrenergically induced glucose uptake in cultured brown adipocytes [46] or in intact mice [47]. In contrast, Inokuma et al.…”
Section: Discussionsupporting
confidence: 76%
“…Although a previous study claimed that norepinephrine‐stimulated uptake of 2‐deoxy‐ 3 H‐glucose is impaired in UCP1‐KO BAT (Inokuma et al , ), a recent report showed that UCP1‐KO mice with reduced BAT temperature and oxygen consumption exhibited normal BAT uptake of 18 F‐FDG in response to CL316243 treatment. Moreover, glycolytic flux and 2‐deoxy‐ 3 H‐glucose uptake in isolated UCP1‐KO brown adipocytes were not affected despite defective uncoupled respiration (Hankir et al , ). Adrenergic stimulation by CL316243 (Hankir et al , ) or by cold exposure (Fig EV3B) appears to increase BAT 18 F‐FDG uptake independent of UCP1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, glycolytic flux and 2‐deoxy‐ 3 H‐glucose uptake in isolated UCP1‐KO brown adipocytes were not affected despite defective uncoupled respiration (Hankir et al , ). Adrenergic stimulation by CL316243 (Hankir et al , ) or by cold exposure (Fig EV3B) appears to increase BAT 18 F‐FDG uptake independent of UCP1. The loss of CPEB2‐promoted Ucp1L translation does not account for decreased 18 FDG uptake in CPEB2‐KO BAT (Fig EV3A).…”
Section: Discussionmentioning
confidence: 99%
“…In the cold stimulation, β 3-AR not only increases glucose transport, but also increases UCP1 expression and activity (Collins et al 2010). Although Hankir MK et al thought that BAT 18 F-FDG uptake and UCP1-mediated heat production can be dissociated (Hankir et al 2017), most studies suggest that UCP1 is necessary for norepinephrine-induced glucose utilization in BAT (Inokuma et al 2005b). The reduction in expression of UCP1 in Lmna G609G/G609G mice further reduced the uptake of 18 F-FDG in BAT.…”
Section: Discussionmentioning
confidence: 99%